Impact Of Covid-19 On the Course of Tuberculosis in Children and Adolescents in Uzbekistan (Eurasian Journal of Research, Development and Innovation, 2023)
The COVID-19 pandemic has had far-reaching consequences on global health systems, with a significant impact on various aspects of healthcare delivery. One area that has been affected is the management and control of tuberculosis (TB), particularly in vulnerable populations such as children and adolescents. Uzbekistan, like many other countries, has faced numerous challenges in addressing the dual burden of TB and COVID-19. This article explores the impact of COVID-19 on the course of tuberculosis in children and adolescents in Uzbekistan, highlighting the challenges faced and potential strategies to mitigate the adverse effects.